The short version of the Sexual Distress Scale (SDS-3): Measurement invariance across countries, gender identities, and sexual orientations - Lin, Chung-Ying; Tsai, Meng-Che; Koós, Mónika; Nagy, Léna; Kraus, Shane W; Demetrovics, Zsolt; Potenza, Marc N; Ballester-Arnal, Rafael; Batthyány, Dominik; Bergeron, Sophie; Billieux, Joël; Briken, Peer; et al. (International journal of clinical and health psychology, 2024)
BACKGROUND: The three-item Sexual Distress Scale (SDS-3) has been frequently used to assess distress related to sexuality in public health surveys and research on sexual wellbeing. However, its psychometric properties and measurement invariance across cultural, gender and sexual subgroups have not yet been examined. This multinational study aimed to validate the SDS-3 and test its psychometric properties, including measurement invariance across language, country, gender identity, and sexual orientation groups. METHODS: We used global survey data from 82,243 individuals (Mean age=32.39 years; 40.3 % men, 57.0 % women, 2.8 % non-binary, and 0.6 % other genders) participating in the International Sexual Survey (ISS; https://internationalsexsurvey.org/) across 42 countries and 26 languages. Participants completed the SDS-3, as well as questions regarding sociodemographic characteristics, including gender identity and sexual orientation. RESULTS: Confirmatory factor analysis (CFA) supported a unidimensional factor structure for the SDS-3, and multi-group CFA (MGCFA) suggested that this factor structure was invariant across countries, languages, gender identities, and sexual orientations. Cronbach's α for the unidimensional score was 0.83 (range between 0.76 and 0.89), and McDonald's ω was 0.84 (range between 0.76 and 0.90). Participants who did not experience sexual problems had significantly lower SDS-3 total scores (M = 2.99; SD=2.54) compared to those who reported sexual problems (M = 5.60; SD=3.00), with a large effect size (Cohen's d = 1.01 [95 % CI=-1.03, -0.98]; p < 0.001). CONCLUSION: The SDS-3 has a unidimensional factor structure and appears to be valid and reliable for measuring sexual distress among individuals from different countries, gender identities, and sexual orientations.